2009
DOI: 10.1021/ja905426e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Space Methods for Powder X-ray Diffraction for Guest−Host Materials: Applications to Cage Occupancies and Guest Distributions in Clathrate Hydrates

Abstract: Structural determination of crystalline powders, especially those of complex materials, is not a trivial task. For non-stoichiometric guest-host materials, the difficulty lies in how to determine dynamical disorder and partial cage occupancies of the guest molecules without other supporting information or constraints. Here, we show how direct space methods combined with Rietveld analysis can be applied to a class of host-guest materials, in this case the clathrate hydrates. We report crystal structures in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
204
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(236 citation statements)
references
References 75 publications
31
204
1
Order By: Relevance
“…The powder patterns for the codeposited samples were refined by the Le Bail method using the profile matching method within FULLPROF (27). The structural analysis of the THF hydrates followed method used in the previously reported work by Takeya et al (28). The direct space method using the FOX (free objects for crystallography) program was used to determine initial THF and methanol positions in the cages (29,30).…”
Section: Methodsmentioning
confidence: 99%
“…The powder patterns for the codeposited samples were refined by the Le Bail method using the profile matching method within FULLPROF (27). The structural analysis of the THF hydrates followed method used in the previously reported work by Takeya et al (28). The direct space method using the FOX (free objects for crystallography) program was used to determine initial THF and methanol positions in the cages (29,30).…”
Section: Methodsmentioning
confidence: 99%
“…4 ( 33.3 3 )). [8,23] Another case is that of Cl 2 hydrate, in which there is ah alogen-bonding interaction, ClÀCl···OH 2 .T he diameter of Cl 2 (5.5 ) is also too large for the sI 5 12 cage, yet ac age occupancy of 32.5 %i sr eported. In each case, guest molecules are isotropically (or randomly)d istributed within the 5 12 cage in the same waya s those of HFC hydrates analyzed in this study.T his gives an indicationt hat these guest molecules are mobile in the 5 12 cage, and bonding between the guests and host water molecules occurs isotropically (or randomly) within the symmetrical 5 12 cage.…”
Section: Host-guestinteractionsmentioning
confidence: 99%
“…The initial crystallographic model for host structuresc omposed of water molecules was introduced from the previously reported models of XRD data of CH 4 hydrate [22] for the directs pace method. [23] The crystal structures, including cage occupancies and distributions of guest molecules within the sI cages,w ere analyzed by using rigid-body constraints for each guest molecule. Because the measured diffraction patterns revealed that the hydrates amples were mixtureso fg as hydrate and as malla mount of unreactedh exagonal ice (Ih) of space group P6 3 /mmc,b ut not the solidified guest molecules, multiphase refinement was performed.…”
mentioning
confidence: 99%
“…Takeya et al have determined structures of clathrate hydrates containing the guests CO 2 , C 2 H 6 , C 3 H 8 , and methyl cyclohexane + CH 4 using X-ray methods with Rietveld analysis [38]. Shin et al [39] have studied clathrate hydrate hosts with methanol guests via X-ray diffraction [39].…”
Section: X-ray Structural Studies Of Clathrate Hydratesmentioning
confidence: 99%